2013
DOI: 10.1007/s10522-013-9466-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of curcuminoids on age-related mitochondrial impairment in female Wistar rat brain

Abstract: The present study demonstrated the neuroprotective effect of curcuminoids, the active polyphenols of Curcuma longa (L.) rhizomes on mitochondrial dysfunctioning in middle aged and aged female Wistar rat brain. Rats were orally treated with curcuminoids (100 mg/kg) for 3 months and their brain was collected for evaluation of mitochondrial enzymes and complexes activity, ultra structural changes in mitochondria, neuronal nitric oxide synthase (nNOS) protein expression, adenosine triphosphate (ATP) and lipofuscin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…The ability of polyphenols to activate lysosomal biogenesis and increase longevity make them an important class of neuroprotective compounds [5,34,37]. In addition, some of the polyphenols like EGCG and curcuminoids reduced the lipofuscin granules in cells, which normally are impossible to degrade or exocytose from the cell [15,289]. Reduction of lipofuscin in the cell can contribute to the restoration of the protein homeostasis by reducing the damage to autophagosomes and proteasomes.…”
Section: Multiple Targets Of Polyphenols Against Admentioning
confidence: 99%
“…The ability of polyphenols to activate lysosomal biogenesis and increase longevity make them an important class of neuroprotective compounds [5,34,37]. In addition, some of the polyphenols like EGCG and curcuminoids reduced the lipofuscin granules in cells, which normally are impossible to degrade or exocytose from the cell [15,289]. Reduction of lipofuscin in the cell can contribute to the restoration of the protein homeostasis by reducing the damage to autophagosomes and proteasomes.…”
Section: Multiple Targets Of Polyphenols Against Admentioning
confidence: 99%
“…Curcumin protects mitochondria from noxious factors such as oxidative stress and rotenone (inhibitor of electron transport chain) in vitro (Daverey and Agrawal, 2016 ; Ramkumar et al, 2017 ). It also alleviates the age-associated loss of mitochondrial and oxidative activity in rodent brains (Dkhar and Sharma, 2010 ; Eckert et al, 2013 ; Rastogi et al, 2014 ). Curcumin also was shown to stimulate Sirt1 and Bcl-2 expression and to decrease brain cell death in experimental stroke (Miao et al, 2016 ).…”
Section: Selected Prominent Medicinal Plants and Plant Genera Used Fomentioning
confidence: 99%
“…It was additionally reported that curcumin seems to exert its beneficial role against neuroinflammation-mediated aging in different models of AD and PD [165,166]. Moreover, it was shown that curcuminoid inhibited age-associated mitochondrial impairment in rats [167] where 100 mg/kg orally-treated curcuminoid inhibited age-associated enzymes such as cytochrome c oxidase, Complex I, NADH dehydrogenase and total ATP content. The curcuminoid, in this way, seems to suppress neuronal-NOS in mitochondria.…”
Section: Curcumin As Nutraceutical Compound In Inflammaging and Brain Inflammagingmentioning
confidence: 96%